PENGARUH PUPUK GUANO DAN N TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays saccharata Strurt) - Harahap, Doni Azhar; Adiwirman, Adiwirman; Yulia, Arnis En (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The objective of this research is to determine the effect guano and N fertilizer and to get the best interaction for the growth and production of sweet corn crops(Zea mays saccharata Sturt). The research was conducted at Experimental Station of the Faculty of Agriculture, University of Riau. The study was conducted for four months from November 2017 until January 2018, implemented withCompletely Randomized Block Design (RAK), Factorial consisting of 2 factors and 3 replications. The first factor of guano fertilizer (G) consists of 3 levels: G0 = guano fertilizer with dose 1.500 kg.ha-1 (600 g/4 m2), G1 = guano fertilizer with dose 2.000 kg.ha-1 (800 g/4 m2), G2 = guano fertilizer with dose 2.500 kg.ha-1(1000 g/4 m2). The second factor of urea (N) consists of 3 levels: N0 = urea with dose 0 kg.ha-1 (0 g/4 m2), N1 = urea with dose 50 kg.ha-1 (20 g/4 m2),N2 = urea with dose 100 kg.ha-1 (40 g/4 m2 ). The observed parameters were plant height, number of leaves, stem diameter, harvesting age, weight of cob/plot weight without cob/plot, length of ear, ear diameter, number of rows of seeds/ear, sugar content in seeds. The results showed guano fertilizer with dose 2.500 kg. ha-1 and urea with dose 100 kg. ha-1 resulted in plant height, number of leaves, stem diameter, harvesting age, the weight of cob/plot weight without cob/plot, length of ear, ear diameter, number of rows of seeds/ear, sugar content in the seeds were higher compared to other treatments. Keywords:Guano Fertilizer, N, Sweet Corn